2017
DOI: 10.1016/j.mod.2017.04.347
|View full text |Cite
|
Sign up to set email alerts
|

Ascl1 promotes tangential migration and confines migratory routes by induction of Ephb2 in the telencephalon

Abstract: During development, cortical interneurons generated from the ventral telencephalon migrate tangentially into the dorsal telencephalon. Although Achaete-scute family bHLH transcription factor 1 (Ascl1) plays important roles in the developing telencephalon, whether Ascl1 regulates tangential migration remains unclear. Here, we found that Ascl1 promoted tangential migration along the ventricular zone/subventricular zone (VZ/SVZ) and intermediate zone (IZ) of the dorsal telencephalon. Distal-less homeobox 2 (Dlx2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Further, a recent study demonstrated that EphB2/EphrinA5 signaling maintains the segregation of the SVZ and SP migratory routes. EphrinA5, highly expressed in the deep ventricular zone (VZ), upper SVZ, deep intermediate zone (IZ) and the CP of the developing telencephalon, confines EphB2-expressing interneurons to the SVZ and SP streams through a repulsive effect ( Liu et al, 2017 ). Similarly, fibronectin leucine-rich transmembrane proteins (FLRT2 and 3), expressed by pyramidal cells and previously known for their roles in axon guidance, excitatory neuron migration and synaptogenesis ( Yamagishi et al, 2011 ; O'Sullivan et al, 2012 ; Leyva-Díaz et al, 2014 ; Del Toro et al, 2017 , 2020 ), have recently been shown to exert repulsive effects on Unc5B/D-expressing cINs in vitro ( Fleitas et al, 2021 ).…”
Section: Extrinsic Guidance Cues Directing Cin Migrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, a recent study demonstrated that EphB2/EphrinA5 signaling maintains the segregation of the SVZ and SP migratory routes. EphrinA5, highly expressed in the deep ventricular zone (VZ), upper SVZ, deep intermediate zone (IZ) and the CP of the developing telencephalon, confines EphB2-expressing interneurons to the SVZ and SP streams through a repulsive effect ( Liu et al, 2017 ). Similarly, fibronectin leucine-rich transmembrane proteins (FLRT2 and 3), expressed by pyramidal cells and previously known for their roles in axon guidance, excitatory neuron migration and synaptogenesis ( Yamagishi et al, 2011 ; O'Sullivan et al, 2012 ; Leyva-Díaz et al, 2014 ; Del Toro et al, 2017 , 2020 ), have recently been shown to exert repulsive effects on Unc5B/D-expressing cINs in vitro ( Fleitas et al, 2021 ).…”
Section: Extrinsic Guidance Cues Directing Cin Migrationmentioning
confidence: 99%
“…In utero electroporation of both Ascl1 and Dlx2 in the dorsal telencephalon of mice promotes tangential migration along the SVZ/VZ and IZ. Further, knockdown of Dlx2 and overexpression of Ascl1 leads to a reduction in the number of INs migrating through the SVZ/VZ, but increases the number of INs migrating through the IZ ( Liu et al, 2017 ). Moreover, chromatin immunoprecipitation assays confirmed that EphB2 receptor, which binds to the repulsive molecule EphrinA5, is a direct downstream target of Ascl1 .…”
Section: Cell-intrinsic Regulation Of Cin Migration Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation